1999
DOI: 10.1115/1.1320819
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Study of the Effect of the Contact Ratio on the Spur Gear Dynamic Response

Abstract: A model was used, where the total gear mesh stiffness was approximated by two constant stiffness levels, in order to analyze the influence of the contact ratio on the dynamic response of spur gears. Due to the stiffness variation there is parametric excitation of the transmission error, which generally causes tooth separation at certain critical rotational speeds. The present paper discloses a method to analytically calculate which contact ratio to use in order to avoid tooth separation near a specific critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…It was observed that increasing the gear contact ratio reduced the dynamic load. This result was also observed by other researchers [30,31] while studying spur gears with symmetric teeth. In these studies, minimum dynamic loads were obtained for contact ratios between 1.8 and 2.0.…”
Section: Resultssupporting
confidence: 86%
“…It was observed that increasing the gear contact ratio reduced the dynamic load. This result was also observed by other researchers [30,31] while studying spur gears with symmetric teeth. In these studies, minimum dynamic loads were obtained for contact ratios between 1.8 and 2.0.…”
Section: Resultssupporting
confidence: 86%
“…Andersson [13] established an approach that can be used to find the contact ratio analytically and use it so as not to avoid tooth separation close to frequencies that could otherwise cause an unbalanced response. Parker and Lin [14] analytically investigated the mesh phasing relationships in epicyclic gears and found that mesh phasing that is present between ring-planet mesh and sun-planet mesh have a significant impact on the static and dynamic behavior of epicyclic gears.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental and analytical results showed the method for choosing a proper contact ratio. Andersson 20 studied the influence of contact ratio on spur gear dynamic response theoretically by calculating the approximate center of the intervals where the response would be unbounded using the number of oscillations, and also gave the method to determine a proper contact ratio in order to eliminate the instability, or at least to reduce the width of the interval of instability near certain critical frequencies. In general, high contact ratio gears minimize dynamic load better than low contact ratio gears.…”
Section: Introductionmentioning
confidence: 99%